“I guess I am not that harsh on myself anymore” : - Foreign Language Anxiety Among Young Finnish Professionals - Mäkinen, Lotta (My University, 2019)
Communication apprehension as a phenomenon has been widely studied, but the earlier research has not explored professionalism as an affecting factor in communication apprehension levels. This study attempts to answer the question “What is the relationship between communication apprehension and the length of full-time employment after the completion of the final degree?”. In addition to the factor of length of full-time employment, the relationship between the levels of communication apprehension (CA) and other factors including amount of English used at work, the subjects’ educational background and biological sex are explored. The target group consisted of 56 young professionals of which 31 were university graduates and 25 university of applied sciences graduates. All subjects were English as a Foreign Language learners with a period of full-time employment varying from 0 to 10 years after completing their final degree. The data was collected through an online questionnaire and further explored with interviews. The methods for the analysis were quantitative and qualitative. The theoretical background introduces earlier research on the topic and creates a basis for the discussion. The quantitative analysis resulted in statistically insignificant relationships between the levels of CA and the factors studied. The analysis did imply that the subjects with a longer period of full-time employment and higher frequency of oral communication in English at work reported lower levels of CA. The educational background factor showed close to non-existent differences in levels of CA and the male target group reported higher levels of CA than the female target group. The qualitative analysis supported the findings of the quantitative analysis. The results suggest that a relationship between length of full-time employment, frequency of English used in oral communication and levels of CA exists, but due to the size of the target group no generalizations can be made.
Keywords: Communication apprehension, Second language acquisition, Foreign language anxiety, Professionalism, English as a foreign language